Variation in Atmospheric Precipitation in Poland in the Years 2001–2018 - Agnieszka Ziernicka-Wojtaszek; Joanna Kopcińska (Atmosphere, 2020)
Climate change scenarios are in agreement as to the direction of air temperature changes in global warming, although the magnitude of the warming depends on the scenario adopted. In contrast, projections of changes in precipitation totals in Poland are not clear and obvious. Analysis of long-term observational series reveals no clear significant trends in levels of precipitation, despite periods of fluctuation, as well as an upward trend reported in the annual amount of precipitation, especially in northern Poland. However, the increasing variability of annual rainfall totals is commonly highlighted. In the years 1861–1990, the coefficient of variation of annual precipitation totals increased from about 10% to 16%. In the years 1971–2000, this coefficient for Poland increased to 17%, and in the period of 2001–2018, which is the subject of the present study, to 19%. Despite the lack of clear trends in annual totals, the increase in the coefficient of variation results in an increase in the frequency of both drought and floods. This unfavorable situation is exacerbated by the downward trend observed in the share of summer rainfall in the annual total. In urban areas with increasing surface sealing, the share of surface runoff in the water balance increases, and in this situation short-term rainfall will cause local flooding.